Starbursts and dusty tori in distant 3CR radio galaxies - Podigachoski, P.; Rocca-Volmerange, B.; Barthel, P.; Drouart, Guillaume; Fioc, M. (Oxford University Press, 2016)
© 2016 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.We present a study of the complete ultraviolet to submillimetre spectral energy distributions (SEDs) of 12 3CR radio galaxy hosts in the redshift range 1.0 < z < 2.5, which were all detected in the far-infrared by the Herschel Space Observatory. The study employs the new spectro-chemical evolutionary code PéGASE.3, in combination with recently published clumpy active galactic nuclei (AGN) torus models. We uncover the properties of the massive host galaxy stellar populations, the AGN torus luminosities, and the properties of the recent starbursts, which had earlier been inferred in these objects from their infrared SEDs. The PéGASE.3 fitting yields very luminous (up to 1013 L?) young stellar populations with ages of several hundred million years in hosts with masses exceeding 1011 M?. Dust masses are seen to increase with redshift, and a surprising correlation - or better upper envelope behaviour - is found between the AGN torus luminosity and the starburst luminosity, as revealed by their associated dust components. The latter consistently exceeds the former by a constant factor, over a range of one order of magnitude in both quantities.